Effect of Income and Expenditure on Foreign Visitors At Indonesian Commercial Tourist Attractions - Saut Maruli Tua Pandiangan (Journal of Social Responsibility, Tourism and Hospitality, 2024)
The purpose of this research is to analyze effect of income and expenditure on foreign visitors at Indonesian commercial tourist attractions. This research is quantitative. Population in this study is 34 Indonesian Provinces in 2021 consisting of Aceh, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Bangka Belitung Islands, Riau Islands, DKI Jakarta, West Java, Central Java, Regional Special to Yogyakarta, East Java, Banten, Bali, West Nusa Tenggara, East Nusa Tenggara, West Kalimantan, Central Kalimantan, South Kalimantan, East Kalimantan, North Kalimantan, North Sulawesi, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo, West Sulawesi, Maluku, North Maluku, West Papua, and Papua from Tourist Attraction Object Statistics 2021 compiled and presented by the Central Statistics Agency. Sampling in this study used saturated samples. So, sample in the research is 34 Indonesian Provinces. The research results show that income has a positive and significant effect on foreign visitors at Indonesian commercial tourist attractions. Expenditure has a negative and not significant effect on foreign visitors at Indonesian commercial tourist attractions.